1997
DOI: 10.1046/j.1471-4159.1997.69062227.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Egr‐1‐Like DNA‐Binding Activities in the Naive Rat Brain and After Excitatory Stimulation

Abstract: Egr-1 and related proteins are inducible transcription factors within the brain recognizing the same consensus DNA sequence. Three Egr DNA-binding activities were observed in regions of the naive rat brain. Egr-1 was present in all brain regions examined. Bands composed, at least in part, of Egr-2 and Egr-3 were present in different relative amounts in the cerebral cortex, striatum, hippocampus, thalamus, and midbrain. All had similar affinity and specificity for the Egr consensus DNA recognition sequence. Adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…One of the hallmarks of the Egr family is transcriptional regulation by neural activity (Beckmann, Davidson, Goodenough, & Wilce, 1997; Honkaniemi & Sharp, 1999). We thus tested the effects of neural activity on transcriptional expression of ApEgr.…”
Section: Resultsmentioning
confidence: 99%
“…One of the hallmarks of the Egr family is transcriptional regulation by neural activity (Beckmann, Davidson, Goodenough, & Wilce, 1997; Honkaniemi & Sharp, 1999). We thus tested the effects of neural activity on transcriptional expression of ApEgr.…”
Section: Resultsmentioning
confidence: 99%
“…Fos induction also correlates with the mossy fibre sprouting (Kiessling & Gass, 1993; Popovici et al, 1990) that occurs during epileptogenesis and may play a role in the subsequent manifestation of seizure symptoms. Like Fos, Egr1 also activates transcription of other genes (Beckmann et al, 1997; Christy & Nathans, 1989) and is considered to play an important role in neuronal plasticity (Knapska & Kaczmarek, 2004). Furthermore, the expression of Fos and Egr1 in seizure onset regions in PWE strongly correlates with interictal spiking (Rakhade et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Egr1 has been suggested as a critical factor for the establishment of long term neuronal plasticity in the hippocampal formation (46 -48). Intriguingly, Egr1 expression is also strongly increased in hippocampal neurons after SE (49,50). In addition, human twin studies showed a dysregulation of Egr1 mRNA expression in idiopathic absence epilepsies (51).…”
Section: Discussionmentioning
confidence: 99%